Explanatory factor analysis on islamic education teachers’ level of technological pedagogical content knowledge (TPACK) at primary schools - Abd. Khaliq (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to measure teachers’ Technological Pedagogical Content Knowledge (TPACK) level and analyze the factors that influence their TPACK level. It was conducted at Islamic primary schools in Gresik Regency, East Java, Indonesia. Involving 246 teachers as a sample, this study employed a mixed-method approach, combining quantitative and qualitative analysis. Quantitative data were analyzed using descriptive analysis and Structural Equation Modeling (SEM) to identify the relationships between variables affecting TPACK. Meanwhile, qualitative data were obtained through in-depth interviews with several teachers to understand their context and experiences in applying TPACK. The results showed that factors such as technology training, institutional support, professional teaching certification, and personal motivation significantly influenced the TPACK level of teachers. These findings provide important insights for the development of more effective training programs and enhanced institutional support to improve teachers' TPACK, aiming to facilitate more interactive and meaningful learning.